Timing in resolution of left heart dilation according to the degree of mitral regurgitation in children with ventricular septal defect after surgical closure - Hwa Jin Cho; Jae Sook Ma; Young Kuk Cho; Byoung Hee Ahn; Kook Joo Na; In Seok Jeong (Elsevier, 2014)
Objective: children with ventricular septal defects (VSD) can have chronic volume overload, which can result in changes of left heart echocardiographic parameters. To evaluate the changes before and after surgical closure, the children were divided into three groups according to the degree of mitral regurgitation (MR), and their echocardiographic characteristics were reviewed at serial follow-up after surgical closure. Methods: the preoperative, and one-, three-, and 12-month postoperative echocardiographic data of 40 children who underwent surgical closure of VSD were retrospectively reviewed. Left ventricular end-diastolic volume (LVEDV), left ventricular end-diastolic dimension (LVEDD), left ventricular end-systolic dimension (LVESD), mitral valvular characteristics, including degree of MR and mitral valve annulus, and left atrial (LA) characteristics, including volume and dimensions, were observed. Results: preoperative LVEDV, LVEDD, LVESD, mitral valvular annulus, LA volume, and LA dimensions were significantly larger in children with MR. Additionally, there were significant decreases in LVEDV, LVEDD, LA volume, and LA dimensions at one, three, and 12 months postoperatively. The degree of MR also improved to a lower grade after surgical closure of the VSD without additional mitral valve repair. Conclusion: the echocardiographic parameters of left heart dilation and MR in children with VSD improved within the first year after surgical closure without additional mitral valve repair. Furthermore, in all of the patients with VSD, regardless of MR, LA dilation was reduced within three months after surgical closure of the VSD; however, LV and mitral valve annular dilatation decreased within 12 months. Resumo: Objetivo: crianças com defeito do septo ventricular (DSV) podem apresentar sobrecarga de volume crônica, que pode resultar em mudanças nos parâmetros ecocardiográficos do coração esquerdo. Para avaliar as mudanças antes e depois do fechamento cirúrgico, as crianças foram divididas em 3 grupos segundo o grau de regurgitação mitral (RM) e suas características ecocardiográficas foram analisadas com acompanhamento em série após o fechamento cirúrgico. Método: revisamos retrospectivamente os dados ecocardiográficos de 40 crianças submetidas a fechamento cirúrgico de DSV antes da cirurgia e nos meses 1, 3 e 12 após a cirurgia. Observamos o volume diastólico final do ventrículo esquerdo (VDFVE), dimensão diastólica final do ventrículo esquerdo (DDFVE) e dimensão sistólica final do ventrículo esquerdo (DSFVE), características da válvula mitral, incluindo grau de RM e o anel da válvula mitral, e características do átrio esquerdo (AE), incluindo volume e dimensões. Resultados: os resultados para VDFVE, DDFVE, DSFVE, anel da válvula mitral, volume do AE e dimensões do AE foram significativamente maiores em crianças com RM. Além disso, não houve redução significativa no VDFVE, DDFVE, volume do AE e nas dimensões do AE nos meses 1, 3 e 12 após a cirurgia. O grau de RM também apresentou melhoria para um grau menor após o fechamento cirúrgico do DSV sem reparo adicional da válvula mitral. Conclusão: os parâmetros ecocardiográficos de dilatação do coração esquerdo e a RM em crianças com DSV haviam apresentado melhora no primeiro ano após o fechamento cirúrgico sem reparo adicional da válvula mitral. Além disso, em todos os pacientes com DSV, independentemente de RM, a dilatação do AE reduziu em três meses após o fechamento cirúrgico do DSV; contudo, a dilatação do VE e do anel da válvula mitral reduziu em 12 meses. Keywords: Ventricular septal defect, Mitral regurgitation, Left heart dilation, Echocardiography, Children, Palavras-chave: Defeito do septo ventricular, Regurgitação mitral, Dilatação do coração esquerdo, Ecocardiografia, Crianças